2008
DOI: 10.2353/ajpath.2008.070730
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Dysfunction and Progressive Retinal Cell Death in SOD1-Deficient Mice

Abstract: The superoxide dismutase (SOD) family is a major antioxidant system, and deficiency of Cu,Zn-superoxide dismutase (SOD1) in mice leads to many different phenotypes that resemble accelerated aging. The purpose of this study was to examine the morphology and physiology of the sensory retina in Sod1 ؊/؊ mice. The amplitudes of the a-and b-waves of electroretinograms elicited by stimuli of different intensity were reduced in senescent Sod1 ؊/؊ mice, and this reduction in amplitude was more pronounced with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 33 publications
2
92
0
Order By: Relevance
“…109 Transgenic mice overexpressing vascular endothelial growth factor have also been used to model ARMD. 110 Finally, Tsubota and colleagues 111,112 showed that mice deficient in Cu, Zn-superoxide dismutase have features typical of the human form of ARMD.…”
Section: New Preclinical Research Directionsmentioning
confidence: 99%
“…109 Transgenic mice overexpressing vascular endothelial growth factor have also been used to model ARMD. 110 Finally, Tsubota and colleagues 111,112 showed that mice deficient in Cu, Zn-superoxide dismutase have features typical of the human form of ARMD.…”
Section: New Preclinical Research Directionsmentioning
confidence: 99%
“…Previous reports have indicated that light exposure induces Sod1 (8) and that the retinas of Sod-1-knockout mice are likely to be impaired by light exposure (9), suggesting that light exposure induces ROS in the retina and evokes retinal degeneration. ROS is related to the regulation of many principal cell functions such as activation of transcription factor (35), gene expression (36), and cell proliferation (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ROS is produced by light exposure in the retina, and it evokes photoreceptor degeneration (8,9); thus, antioxidants such as dimethylthiourea (10), phenyl-N-tert-butyl nitrone (11), and 2,2,6,6-tetramethyl-4-piperidinol-1-oxyl (12) have been reported to be effective in animal experiments. Astaxanthin, a carotenoid, is present in many wellknown seafoods such as salmon, trout, red sea-bream, shrimp, lobster, and fish eggs.…”
Section: The Protective Effects Of a Dietary Carotenoid Astaxanthinmentioning
confidence: 99%
“…This may amplify the inflammatory process leading to additional RPE cell damage, potentially producing a state of chronic inflammation . Knockout of antioxidative genes in mice (Sod1À/À mice, Sod2 knockdown mice, and Nrf2À/À mice) results in the development of the typical features of AMD (Hashizume et al 2008;). Genetically, polymorphism in a number of genes, including members of the complement pathway, apolipoprotein E (ApoE), ARMS2, HTRA1, CX3CR1, VEGF-A, and ABCA4 have been associated with AMD, indicating the involvement of inflammation, lipid metabolism, RPE dysfunction, and angiogenesis in AMD (Ding et al 2009).…”
Section: Corticosteroidsmentioning
confidence: 99%